Formulation and Determination of Sun Protection Factor (SPF) of Sunscreen Gel Preparations Containing Epigallocatechin Gallate (EGCG) Using the Spectrophotometric Method - Oppy Aesaiw (Strada Journal of Pharmacy, 2019)
Long-term exposure to the sun causes various kinds of abnormalities in human skin so it requires skin protection from the outside. Sunscreen is a cosmetic therapy that can shield the skin and face against UV radiation, including the potential to induce accelerated ageing, sunburn, and skin cancer. Tea leaf-derived polyphenol compounds, particularly EGCG, have the most potent and plentiful antioxidant action. The objective of this work is to investigate the impact of variations in epigallocatechin gallate (EGCG) levels on the physical properties and effectiveness of sunscreen gel. This study used an experimental design with four EGCG gel formulas (negative control (0%), F1 (0.1%), F2 (0.2%), F3 (0.4%)) and tested with a UV-Vis spectrophotometer with the resulting absorbance calculated using the Mansur formula.The results showed that the SPF value increased with increasing EGCG concentrations (negative control, F1, F2, F3, positive control: 18.94 (moderate), 22.55 (moderate), 29.10 (moderate), 41.58 (high), 48.11 (high)). The highest SPF value on Formulation 3 indicates a high level of sunscreen capability. EGCG gel with a concentration of 0.4% has good physical characteristics (slightly thick texture, odorless, transparent white color, homogeneous, pH 6.57, adhesion 3.30, diffusion 6.36) and the highest SPF value (41.58). The statistical test using Kruskall-Wallis followed by the Man-Whitney test showed a significant difference in a p-value of 0.05.